Does integument arise de novo or from pre-existing structures? ── Insights from the key regulatory genes controlling integument development - Jiang, Min; Jian, Jinjing; Zhou, Chengchuan; Li, Linfeng; Wang, Yuguo; Zhang, Wenju; Song, Zhiping; Yang, Ji (Frontiers in Plant Science, 2023)
The origin of seeds is one of the key innovations in land plant evolution. Ovules are the developmental precursors of seeds. The integument is the envelope structure surrounding the nucellus within the ovule and developing into the seed coat when ovules mature upon fertilization. The question of whether the integument arise de novo or evolve from elaboration of pre-existing structures has caused much debate. By exploring the origin and evolution of the key regulatory genes controlling integument development and their functions during both individual and historical developmental processes, we showed the widespread presence of the homologs of ANT, CUC, BEL1, SPL, C3HDZ, INO, ATS, and ETT in seedless plant genomes. All of these genes have undergone duplication-divergence events in their evolutionary history, with most of the descendant paralogous suffering motif gain and/or loss in the coding regions. Expression and functional characterization have shown that these genes are key components of the genetic program that patterns leaf-like lateral organs. Serial homology can thus be postulated between integuments and other lateral organs in terms of the shared master regulatory genes. Given that the genetic program patterning leaf-like lateral organs formed in seedless plants, and was reused during seed origin, the integument is unlikely to arise de novo but evolved from the stem segment-specific modification of pre-existing serially homologous structures. The master ‘switches’ trigging the modification to specify the integument identity remain unclear. We propose a successive transformation model of integument origin.